Synergistic antioxidant effects of natural compounds on H2O2-induced cytotoxicity of human monocytes - Ben Mrid, Reda; Bouchmaa, Najat; Ouedrhiri, Wessal; Ennoury, Abdelhamid; ZouaouI, Zakia; Kabach, Imad; Nhiri, Mohamed; El Fatimy, Rachid (Frontiers in Pharmacology, 2022)
Natural compounds are endowed with a broad spectrum of biological activities, including protection against Toxins. Most of them are known for their antioxidant and radical scavenging activities. However, the synergistic combination of these natural molecules is not well studied. Therefore, the present study aims first to investigate the effect of four potent natural molecules (rosmarinic acid (Ros-A), ellagic acid (Ella-A), curcumin (Cur), and syringic acid (Syr-A)) on H2O2 -induced cell cytotoxicity and oxidative stress on the human monocytes (THP-1) and then to evaluate their combined action effect. Optimal combinations of these molecules were predicted using an augmented mixture design approach. In the first, as preliminary antioxidant activities screening, two in vitro assays were adopted to assess the single radicals scavenging activity of these natural compounds, DPPH• and ABTS•+ tests. Based on the results obtained, the multitude of optimal formulas proposed by the mixture design study led to choosing four potent compositions (comp) in addition to ellagic acid, proposed as the most efficient when applied alone. The different molecules and mixtures were used to assess their cytoprotective effect on THP-1 cells in the presence and absence of H2O2. The most potent Comp-4, as well as the molecules forming this mixture, were exploited in a second experiment, aiming to understand the effect on oxidative stress via antioxidant enzyme activities analysis in the H2O2-induced oxidative stress in the THP-1 cell line. Interestingly, the natural molecules used for THP-1 cells treatment exhibited a significant increase in the antioxidant defense and glyoxalase system as well as suppression of ROS generation evaluated as MDA content. These results indicate that the natural compounds tested here, especially the synergistic effect of Cur and Ros-A (Comp-4), could serve as cytoprotective and immunostimulant agents against H2O2-induced cytotoxicity THP-1 cells, which makes them interesting for further investigations on the molecular mechanisms in preclinical animal models.